2023
DOI: 10.1021/acsaem.2c03944
|View full text |Cite
|
Sign up to set email alerts
|

Molten Sodium Penetration in NaSICON Electrolytes at 0.1 A cm–2

Abstract: High-conductivity solid electrolytes, such as the Na superionic conductor, NaSICON, are poised to play an increasingly important role in safe, reliable battery-based energy storage, enabling advanced sodium-based batteries. Coupled demands of increased current density (≥0.1 A cm–2) and low-temperature (<200 °C) operation, combined with increased discharge times for long-duration storage (>12 h), challenge the limitations of solid electrolytes. Here, we explore the penetration of molten sodium into NaSICON at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 63 publications
1
12
1
Order By: Relevance
“…Recent studies have shown that Mode II penetration due to small levels of electronic conductivity may lead to significant metal penetration in solid electrolytes. 45,65 Since the cells in this work only had current applied in one direction, distinct stripping and plating interfaces could be observed, and these two penetration modes could be distinguished. In Figure 3b, large dark regions could be seen at the top electrolyte interface (plating interface�Mode I driven) and a few smaller dark regions were observed disconnected from either interface (Mode II driven).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Recent studies have shown that Mode II penetration due to small levels of electronic conductivity may lead to significant metal penetration in solid electrolytes. 45,65 Since the cells in this work only had current applied in one direction, distinct stripping and plating interfaces could be observed, and these two penetration modes could be distinguished. In Figure 3b, large dark regions could be seen at the top electrolyte interface (plating interface�Mode I driven) and a few smaller dark regions were observed disconnected from either interface (Mode II driven).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…A previous study found that both degradation mechanisms became relevant at these high current densities, and this study confirmed that observation. 45 In regard to Figure 3c, it is important to note that the ridge observed near the stripping interface in Figure 3b blocked the X-rays for EDS and made elemental mapping of the region containing Mode II penetration challenging.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations